The pedagogic domain and epistemic access in South African higher education: The challenges for students with disabilities during the COVID-19 pandemic - Ndlovu, S. (South African Journal of Higher Education, 2022)
The unexpected emergence of COVID-19 pandemic has had adverse effects on diverse students’ epistemic access in the context of South African higher education. While this has seen an increasing urge for research to understand epistemic access and success of disadvantaged students, there has not been a specific focus on the issue as it specifically relates to students with disabilities, who are unique in their own way, thereby requiring an intervention that considers their differences. Using the decolonial analytical framework, the article explored the challenges in the pedagogic domain, and their implications for the epistemic access of students with disabilities during the pandemic. Data were collected through the synthesis of international and South African literature on the issue, as it specifically relates to students with disabilities during the pandemic. The key finding was that the pandemic exacerbated the pedagogic challenges already confronted by students with disabilities, thereby gravely affecting their access to learning. The objective of the article was to present the pedagogic challenges and how they have limited students with disabilities’ epistemic access, as exacerbated by the pandemic. This was so that interventions that could assist their learning in the “new normal”, could be thought about, in the South African context, in Africa and globally.